Blockchain-Based Verifiable Computation: A Review - Zara, Maham; Wang, Shuzhen; ul Moin, Hasan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Verifiable computation has been studied as a way to verify the outcomes of an outsourced computation. It is usually seen from the view of a user who wishes to outsource computation to a centralized third party but wants to ensure that the party provides correct results. With the said scheme, the verifier requests the prover to perform the computational task and then verifies the outcome by checking the output and the proof obtained from the prover. However, there are several security challenges within a centralized third party to execute verification tasks. Recently, the advancement in blockchain technology has offered an opportunity to solve these security challenges. Blockchain is a distributed ledger and decentralized technology that eliminates the need for third-party verification. In recent years, the emergence of innovative applications of verifiable computing techniques within blockchain technology has been witnessed. These applications focus on ensuring secure key management, enhancing smart contracts, and fortifying sybil-resistance. The use of blockchain in the realm of verifiable computing has drawn the attention of many researchers. However, our research into relevant papers revealed a notable lack of comprehensive surveys on blockchain-based verifiable computing in the literature. To overcome this gap, we conducted a comprehensive survey on blockchain-based verifiable computation. First, we address fundamental concepts related to blockchain-based verifiable computation. Afterwards, we offer a series of criteria to evaluate existing blockchain-based verifiable computation techniques. Finally, based on our comprehensive review and evaluation metrics, we explore various open challenges and potential research prospects. These include zero-knowledge proofs (ZKP) integration, addressing privacy preservation, scalability, and traceability. Future research should focus on robust privacy-preserving methods, using ZKP for enhanced security, off-chain computations for scalability, and decentralized file systems like Interplanetary File System (IPFS) to improve traceability.